Do Remittances to Latin America Depend on the U.S. Business Cycle? - Gradzka, Ewa.; Roache, Shaun (Washington, D.C. : International Monetary Fund, 2007)
We use a range of methods and remittance data from 1990 to 2007 to assess the strength and significance of linkages between remittance flows to Latin America and the U.S. business cycle. All of the evidence suggests that remittance flows are relatively insensitive to fluctuations in the U.S. cycle, underlining their role as a stable source of external financing, in good times and bad. A number of factors, notwithstanding uncertainties related to official remittance data reliability, might explain this result, including remittance smoothing and flexible immigrant labor markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet